2021
DOI: 10.48550/arxiv.2102.05566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Layer VQE: A Variational Approach for Combinatorial Optimization on Noisy Quantum Computers

Xiaoyuan Liu,
Anthony Angone,
Ruslan Shaydulin
et al.

Abstract: Combinatorial optimization on near-term quantum devices is a promising path to demonstrating quantum advantage. However, the capabilities of these devices are constrained by high noise levels and limited error mitigation. In this paper, we propose an iterative Layer VQE (L-VQE) approach, inspired by the Variational Quantum Eigensolver (VQE). We present a large-scale numerical study, simulating circuits with up to 40 qubits and 352 parameters, that demonstrates the potential of the proposed approach. We evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Amongst the most widely used algorithms for this type of procedure are the Variational Quantum Eigensolver (VQE) [56] and the Quantum Approximate Optimization Algorithm (QAOA) [57]. Both of these algorithms are classicalquantum hybrid algorithms, i.e., they combine the use of a classical computer with a (smaller) quantum computer which can further improve the applicability of these algorithms on current quantum computing devices [58].…”
Section: ) Quantum Algorithmsmentioning
confidence: 99%
“…Amongst the most widely used algorithms for this type of procedure are the Variational Quantum Eigensolver (VQE) [56] and the Quantum Approximate Optimization Algorithm (QAOA) [57]. Both of these algorithms are classicalquantum hybrid algorithms, i.e., they combine the use of a classical computer with a (smaller) quantum computer which can further improve the applicability of these algorithms on current quantum computing devices [58].…”
Section: ) Quantum Algorithmsmentioning
confidence: 99%
“…Commonly studied VQAs include Quantum Neural Networks (QNNs) [13] used to perform classification tasks in machine learning, and Variational Quantum Eigensolvers (VQEs) that are used to find the ground state of a given Hamiltonian from physics or chemistry [26]. Variational Quantum Eigensolvers have gained particular interest: with applications to quantum chemistry [6], or to combinatorial optimization [12,22]. The quantum systems used in VQEs are challenging to classically simulate so there is a promising possibility of quantum computational advantages for these important applications.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from that, the choice of structure is also limited by hardware constraints like the topology of a certain quantum device. While the model structure is an important factor in training VQAs that has received much attention in the QML community [27][28][29][30][31][32][33], the authors of [34] have shown that the technique used to encode data into the model plays an equally important role, and that even highly expressive structures fail to fit simple functions with an insufficient data-encoding strategy. A less explored architectural choice in the context of QML is that of the observables used to read out information from the quantum model.…”
Section: Introductionmentioning
confidence: 99%